P73 ANGIOGRAPHY–DERIVED INDEX OF MICROVASCULAR RESISTANCE (IMR–ANGIO) IN TAKOTSUBO SYNDROME. (18th May 2022) - Castaldi, G; Fezzi, S; Widmann, M; Mammone, C; Rizzetto, F; Lia, M; Prati, D; Pighi, M; Pesarini, G; Tavella, D; Scarsini, R; Ribichini, F
Abstract: Introduction: Coronary microvascular dysfunction (CMD) has been proposed as a key driver in the etiopathogenesis of Takotsubo syndrome (TTS), likely related to an "adrenergic storm" upon a susceptible microvascular circulation. The aim of our manuscript was to assess and quantify CMD in patients with TTS through non–invasive angio–derived index of microcirculation (IMRangio) and evaluate its correlation with clinical and instrumental presentation. Methods: 41 consecutive TTS patients were retrospectively analyzed. Three different formulas for compute Non–Hyperemic IMRangio (NH–IMRangio) derived by 3D–Quantitative Coronary Angiography (3D–QCA) and Quantitative Flow Reserve (QFR) analysis were used according to each fluidodynamic mathematical expression as reported by respective authors. CMD was deﬁned as an IMRangio ≥ 25. The correlation between NH–IMRangio and clinical presentation and the comparation between the three formulas were provided. Results: Median age was 76 years, 85.7% were women and mean left ventricular ejection fraction (LVEF) at first echocardiogram was 41.2%. NH–IMRangio was higher in Left Anterior Descending artery (LAD) than Circumflex artery (CX) and Right Coronary artery (RCA) with either NH–IMRangio 1 (52.7 vs 35.3 vs 41.4), NH–IMRangio 2 (47.2 vs 31.8 vs 37.3) or NH–IMRangio 3 (52.7 vs 36.1 vs 41.8). All patients presented CMD with NH–IMR angio ≥ 25 in at least one territory with each formula. NH–IMRangio in LAD territory was significantly higher in patients presenting with LVEF impairment (≤40%) than in those with preserved ventricular global function (NH–IMRangio LAD 1: 59.3 vs 46.3, p. value=0.030; NH–IMRangio LAD 2: 52.9 vs 41.4, p–value=0.037; NH–IMRangio LAD 3: 59.2 vs 46.3, p–value=0–035). Association between NH–IMRangio computed in LAD and LVEF showed a moderate correlation (NH–IMRangio 1: r = –0, 3485, Rho = 0, 1214, p = 0, 0256; NH–IMRangio 2: r = –0, 3513; Rho = 0, 1234, p = 0, 0256; NH–IMRangio 3: r = –0, 3326, Rho = 0, 1106, p = 0, 0336). Finally, Bland–Altman plot analysis showed good agreement between NH–IMRangio 1 and 3, while NH–IMRangio 2 showed a consistent bias of –5 units against both NH–IMRangio 1 and NH–IMRangio 2 with increasing difference at higher absolute values. Conclusion: CMD, assessed with NH–IMRangio, is a common finding in TTS and it is inversely correlate with LVEF dysfunction. The available formulas for NH–IMRangio computation have a substantial superimposable diagnostic performance in assessing CMD.